2007
DOI: 10.1021/mp070050b
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Targeted Dinitrophenyl Hapten Immunotherapy: Effect of Linker Chemistry on Antitumor Activity and Allergic Potential

Abstract: Targeting of malignancies with folate-linked therapeutics has proven to be a promising endeavor due to the preferential expression of folate receptors (FR) on human tumors. We have shown that folic acid (pteroyl-glutamate) can be used to deliver an antigenic hapten, fluorescein, to the surface of tumor cells to promote their opsonization within a fluorescein-immunized host. Here, we investigate structure-activity relationships among members of another class of folate-hapten conjugates ( EC57, EC63, EC0293, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 30 publications
1
54
0
Order By: Relevance
“…In a previous publication, DNPimmunized mice were found to produce anti-DNP IgE antibodies, and folate-DNP conjugates with identical hapten linker chemistry to that found in KLH-DNP (i.e. the immunogen) were found to cause allergy in a rat PCA assay (8). As most allergic and hypersensitivity reactions are associated with Th2-biased immune responses, the formation of allergen-specific IgE antibody is a hallmark of allergic sensitization (20,21).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In a previous publication, DNPimmunized mice were found to produce anti-DNP IgE antibodies, and folate-DNP conjugates with identical hapten linker chemistry to that found in KLH-DNP (i.e. the immunogen) were found to cause allergy in a rat PCA assay (8). As most allergic and hypersensitivity reactions are associated with Th2-biased immune responses, the formation of allergen-specific IgE antibody is a hallmark of allergic sensitization (20,21).…”
Section: Discussionmentioning
confidence: 96%
“…While dosing folate-FITC early during immunization served the purpose of eliminating any allergic response in immunized animals regardless of immunogen dose, the impact that this maneuver had on antitumor activity was called into question. We have previously shown that the administration of folate-FITC supplemented with low to moderate doses of IL-2 ±IFN-α can generate cures or significantly extend the lifespan of FITC-immunized, M109 tumor-bearing mice (7,8). The M109 tumor is a weakly immunogenic FR-positive subclone of the Madison lung carcinoma cell line that requires regular passages in Balb/c mice (19).…”
Section: Increasing Immunogen Dose and Dosing Folate-fitc Early Allevmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, haptens have been tested as a treatment of cancer several times in the past. In this review, we examine the four main concepts of hapten-mediated antitumor treatment: (1) ex vivo haptenation [2131], (2) in situ haptenation [32, 33], (3) epifocal hapten application [34–42], and (4) antigen-hapten administration [4347]. Despite the wealth of experiments in this field, the mechanisms underlying these treatment approaches are largely unclear and require further study.…”
Section: Introductionmentioning
confidence: 99%